Literature Study on the Challenges and Successes of Augmented Reality Implementation in Studying Arabic Mufradat - Azmi Zulkarnain, Raihan; Tatang, Tatang; Saleh, Nalahuddin; Abdurrahman , Ahnaf (Universitas Cokroaminoto Palopo, 2025)
Despite facing significant challenges, Augmented Reality (AR) has proven to be a highly effective and promising tool for revitalizing Arabic vocabulary (mufradat) learning. Generally, AR is a major success because it creates a more interactive and engaging learning environment, which in turn significantly boosts students' motivation, interest, and comprehension. This key success stems from AR's ability to provide 3D visualization of the mufradat, making it much easier for students to memorize and understand abstract word meanings while bridging the gap between theory and practice. The positive impact is clearly visible in the increase in students' average test scores, the strengthening of vocabulary mastery, and the improvement of speaking skills (maharah kalam). However, this progress is met with major challenges, both pedagogical and technical. Pedagogical issues include conventional methods being monotonous and unappealing, students struggling to master and recall vocabulary, and the problem of insufficient teacher readiness in using the new technology. Technical constraints, on the other hand, involve limited AR content, issues with device compatibility (often restricted to the Android system), and the high error rate in text recognition. Therefore, while AR is a powerful solution for overcoming traditional challenges, it requires ongoing development and infrastructural support.